Presumed Neuroglycopenia Caused by Severe Hypoglycemia in Horses - Aleman, M. (J Vet Intern Med, 2018)
BACKGROUND: Neuroglycopenia refers to a shortage of glucose in the brain resulting in neuronal dysfunction and death if left untreated. Presumed neuroglycopenia has not been described in horses. OBJECTIVE: To report neurological signs in horses with presumed neuroglycopenia as the result of severe hypoglycemia. ANIMALS: Ninety horses (hours to 28 years of age) diagnosed with hypoglycemia (blood glucose concentration < 75 mg/dL [< 4.2 mmol/L]). METHODS: Retrospective study. Electronic medical records were searched. Signalment, history, complaint, clinical signs, laboratory findings including CSF analysis, electroencephalogram, clinical or definitive diagnosis, and outcome were recorded. Kruskal‐Wallis analysis of variance and logistic regression were used to investigate association between blood glucose concentration and data extracted. Statistical significance was set at P < 0.05. RESULTS: Thirty‐eight and 52 horses had mild (50‐74 mg/dL [2.8‐4.1 mmol/L]), and severe hypoglycemia (< 50 mg/dL [< 2.8 mmol/L]), respectively. Most common causes of hypoglycemia included liver and gastrointestinal (40%) disease, sepsis (33%), neoplasia (7%), and insulin‐induced (4%). Most common neurologic deficits included obtundation (100%), seizures (42%), and disorientation (22%). CSF‐glucose was severely low (mean 2.5 mg/dL [0.1 mmol/L], median 0 mg/dL). Paroxysmal discharges in support of seizures were identified in the occipital (visual) and parietal (closest to temporal‐auditory) cortical regions upon EEG examination (8/8 horses). CONCLUSIONS AND CLINICAL IMPORTANCE: Neuroglycopenia is presumed to occur in horses as the result of severe hypoglycemia. Subclinical seizures, and intermittent blindness and deafness of cortical origin can occur. Severe altered state of consciousness and seizures can be observed at a blood glucose cut‐off value of < 42 mg/dL (< 2.3 mmol/L).